2018
DOI: 10.1186/s12884-018-1671-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality medicines in maternal health: results of oxytocin, misoprostol, magnesium sulfate and calcium gluconate quality audits

Abstract: BackgroundThe high level of maternal mortality and morbidity as a result of complications due to childbirth is unacceptable. The impact of quality medicines in the management of these complications cannot be overemphasized. Most of those medicines are sensitive to environmental conditions and must be handled properly. In this study, the quality of oxytocin injection, misoprostol tablets, magnesium sulfate, and calcium gluconate injections was assessed across the six geopolitical zones of Nigeria.MethodSimple, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 29 publications
3
52
3
2
Order By: Relevance
“…Unfortunately, these medicines are very sensitive to environmental conditions like high temperatures (oxytocin, [8][9][10]) and humidity (misoprostol, [11,12]). Most oxytocin products should be stored at 2-8°C according to the labelling, and this can be challenging, especially in rural areas in LMICs [13][14][15][16]. Since misoprostol tablets can be stored at room temperature and can be administered orally, they offer an alternative to oxytocin injections in places where appropriate storage conditions for oxytocin cannot be ensured, or where no trained staff is available to administer medicines parenterally [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these medicines are very sensitive to environmental conditions like high temperatures (oxytocin, [8][9][10]) and humidity (misoprostol, [11,12]). Most oxytocin products should be stored at 2-8°C according to the labelling, and this can be challenging, especially in rural areas in LMICs [13][14][15][16]. Since misoprostol tablets can be stored at room temperature and can be administered orally, they offer an alternative to oxytocin injections in places where appropriate storage conditions for oxytocin cannot be ensured, or where no trained staff is available to administer medicines parenterally [17].…”
Section: Introductionmentioning
confidence: 99%
“…1 Structures of oxytocin (modified from [2]) and of misoprostol, and their typical degradation mechanisms. Commercial misoprostol is a mixture of the depicted structure at its epimer at C 16 , and of the enantiomers of both compounds. Corresponding stereoisomers are found for the degradation products of misoprostol Several previous studies have shown that the quality of oxytocics, especially in low and middle-income countries (LMIC), is often poor [8,11,15,16,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A major problem of oxytocin relates to heat-related degradation, inappropriate storage in the supply chain and at the health facilities. In most low-income countries these storage conditions are usually very difficult to maintain[9,10]. Surveillance studies have shown high prevalence of poor-quality oxytocin, particularly in Africa and Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance studies have shown high prevalence of poor-quality oxytocin, particularly in Africa and Asia. [1012] Most common problems were insufficient or no active ingredient[10,11]. Safe medicines supply is fundamental to public health[13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation